Monitoring and assessment of the impact of natural hazards of infrastructure resilience using earth observation techniques - Tzouvaras, Marios (Department of Civil Engineering and Geomatics, Faculty of Engineering and Technology, Cyprus University of Technology, 2020)
Infrastructure is designed to be operational under normal circumstances and to cope with common natural disruptions such as rainfall, snow and excessive heat. However, extreme natural hazards can lead to severe problems not only at the areas where such events occur, but also at neighbouring regions or even the entire country. The main aim of this PhD thesis is the development of a novel methodology for the identification of areas susceptible to land movements and the systematic monitoring of land displacement at areas of interest in Cyprus, such as areas with critical infrastructure, areas of Cultural Heritage (UNESCO sites) and other urban areas, through Earth Observation (EO) techniques. Freely available Copernicus data such as those from the Sentinel missions and datasets from other Copernicus contributing missions (Landsat TM), as well as open-source European Space Agency (ESA) SNAP software were used in the entire process. Three case study areas were selected based on the site geology and the risk that land movements can cause to the general public, critical infrastructure and to Cultural Heritage monuments. The development of landslide hazard maps was carried out, in one case study area, via the Analytic Hierarchy Process (AHP) methodology, using Landsat ΤΜ imagery. Coherent Change Detection (CCD) and Differential Interferometric SAR (DInSAR) methods, exploiting a series of Sentinel-1 SAR images, were used for monitoring land displacement caused by earthquakes and landslides, affecting different areas in Cyprus. For the calibration of the proposed EO based methodology, and the validation of the results obtained through the DInSAR processing of Sentinel-1 acquisitions, coordinates from the permanent Global Navigation Satellite System (GNSS) stations of the Cyprus Positioning System (CYPOS) network, operated by the Department of Lands and Surveys were used. The main outcome of this PhD thesis is the development of a novel Earth Observation based methodology integrating the CCD and DInSAR techniques for the systematic identification of areas susceptible to natural hazards, such as earthquakes and landslides, and the continuous monitoring of such land displacement phenomena based on the analysis of optical and Synthetic Aperture Radar (SAR) satellite data, leading to a systematic way of monitoring land movements on a larger scale. Rapid detection and more detailed multi-pass products were developed using the proposed DInSAR and CCD methodologies, for the detection and monitoring of natural hazards and their impact on critical infrastructure resilience. The proposed methodology might lay the foundations for the development of an automated Early Warning System that will facilitate the operation of the country’s emergency mechanism and warn public authorities and the general public in a timely manner for an upcoming danger. Moreover, it can also serve as a guidance/consultation tool for public authorities and decision-makers regarding the identification of high-risk areas in terms of land displacement on time and the adoption of preventive protection measures on Cultural Heritage landscapes and critical infrastructure.
Keywords: Coherence; Infrastructure resilience; Land displacement; Natural hazards; SAR interferometry